New Plants for Florida: Sweet Corn - Brian Scully; Richard L. Jones; Mary Duryea; Berry J. Treat (EDIS)
Today, the sweet corn industry is one of the most robust vegetable industries in Florida, and nationally, sweet corn is ranked second in consumption after tomato. Florida production uses about two dozen hybrids derived from about six different breeding programs. Over the years, the FAES breeding program has contributed an array of products, including hybrids and inbreds, along with germplasm that serves as the raw material for the development of future hybrids. This document is part of Circular 1440, a publication of the Florida Agricultural Experiment Station, the Agronomy Department and IFAS Communication Services, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date August 2003. Originally published as a booklet by IFAS Communication Services June 2003.